2003
DOI: 10.1123/japa.11.3.408
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Evaluation of the Canadian Centre for Activity and Aging’s Home Support Exercise Program for Frail Older Adults

Abstract: The Home Support Exercise Program (HSEP) targets frail older adults. After a 4-hr training workshop, home-support workers (HSWs) encourage clients to do a simple, progressive set of 10 exercises during regular visits. Exercise compliance and functional performance were examined in 60 clients who received the HSEP, compared with 38 clients whose HSWs had not received HSEP training. Both groups were primarily female, average age 82, and many of them used walking aids. The 40 HSEP clients who continued with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 25 publications
1
37
0
Order By: Relevance
“…Five of those six [4,7,15,30,75] reported affective improvements in addition to physiological improvements. However, four of the nine studies which did not assess physical improvement [16,41,47,77] reported affective improvement, and two of the nine [8,40] reported partial improvements.…”
Section: Studies Applying General Non-specific Physical Activitymentioning
confidence: 98%
See 3 more Smart Citations
“…Five of those six [4,7,15,30,75] reported affective improvements in addition to physiological improvements. However, four of the nine studies which did not assess physical improvement [16,41,47,77] reported affective improvement, and two of the nine [8,40] reported partial improvements.…”
Section: Studies Applying General Non-specific Physical Activitymentioning
confidence: 98%
“…Eleven studies were included in the second group, which examined the effect of strength training on affect [17,18,20,29,49,57,[65][66][67][68]74], and 15 studies on non-specific physical activity or mindful activities such as yoga or Tai Chi were included in the third group [4,7,8,10,15,16,18,30,40,47,41,56,58,75,77]. One study [57] compared aerobic and resistance training to a control group in reducing depression and thus was included in both the first and second group.…”
Section: Review Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a common limitation for following frail participants over time, which is expected (Johnson, Myers, Scholey, Cyarto, & Ecclestone, 2003).…”
Section: Limitationsmentioning
confidence: 99%